IMMEDIATE RESTORATION CUSTOM-MADE BY ADDITIVE MANUFACTURING ABOUT DENTAL IMPLANTS: PREDICTABLE RESULTS FOR PINK AND WHITE ESTHETICS - Matos, Jefferson David Melo de; Coser, Raphael Castiglioni; Rodrigues, Michael Frank; Cabral, Guilherme; Viaro, Thiago R V; Queiroz, Daher Antonio; Maciel, Lucas Campagnaro (Brazilian Journal of Implantology and Health Sciences, 2024)
The definition of dental implant failure has evolved from focusing solely on lack of osseointegration to encompass broader concerns such as aesthetics. However, the criteria for aesthetic failure in implant dentistry are not well defined. Although several aesthetic indices have been validated to objectively evaluate clinical outcomes, including failure of an implant-supported crown. In this sense, aesthetic flaws in implant dentistry can be categorized into pink and white tissue flaws. This study aims to describe an extensive rehabilitation protocol where implants were placed using printed surgical guides and adaptations for bone and tissue grafts, facilitating restoration in the aesthetic zone. Key clinical stages and aspects are illustrated through the case of a fractured upper left central incisor, where an implant system was used for immediate patient rehabilitation. By highlighting these crucial steps and considerations, this study underscores the effectiveness of immediate implantation and restoration techniques in achieving optimal aesthetic and functional outcomes in dental rehabilitation